Pengaruh Brand Image Terhadap Loyalitas Pelanggan Melalui Kepuasan Konsumen (Studi Kasus Toko Sembako H. Kastari Putra) - Nisak, Iif Hilyatun; Hidayati, Nur; Dianawati, Eris (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the influence of Brand Image on customer loyalty through customer satisfaction at H. Kastari Putra Grocery Store in Jombang Regency. The background of this research is based on the importance of building and maintaining customer loyalty in the face of increasingly intense competition in the grocery retail business. Brand Image is considered a key factor that shapes customer perceptions, which ultimately affects their satisfaction and loyalty. This research uses a quantitative method by collecting data through questionnaires distributed to customers of H. Kastari Putra Grocery Store. Data analysis is conducted using statistical methods to examine the relationship between brand image, customer satisfaction, and customer loyalty. The results of this research are expected to provide theoretical contributions to the development of marketing management science, particularly regarding the role of Brand Image and customer satisfaction in building customer loyalty in the grocery retail sector. Practically, the findings of this study offer strategic recommendations for store owners and other retail business actors to enhance Brand Image and customer satisfaction in order to create sustainable customer loyalty. Keyword: Brand Image, Customer Loyalty, Customer Satisfaction